2016
DOI: 10.15420/icr.2016.11.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Imaging in the Catheter Laboratory: Real-time Fusion of Echocardiography and Fluoroscopy During Percutaneous Structural Heart Disease Interventions

Abstract: Percutaneous catheter-based techniques for the treatment of structural heart disease are becoming more complex, and current imaging techniques have limitations: while fluoroscopy gives poor visualisation of cardiac anatomical structures, echocardiography is limited in its ability to detect the position of catheters and devices. The EchoNavigator® (Philips) live image guidance tool is a novel system that integrates real-time echocardiography with fluoroscopic X-ray imaging, optimising the guidance and positioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…From a theoretical perspective, it should be an advantage to combine and fuse the complementary information of different imaging modalities like ultrasound and fluoroscopy instead of only simultaneously displaying these images on separate screens. Therefore, several technical solutions for fusion imaging have been established that are nowadays commercially available [ 3 – 5 ]. However, to date, there are only a very limited number of studies which have shown the feasibility and safety of dynamic fusing imaging of TEE and fluoroscopy during cardiac interventions [ 6 ], and only one small study with a number limitations has pointed out towards a clinical advantage of the use of FI during interventional LAA closure [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a theoretical perspective, it should be an advantage to combine and fuse the complementary information of different imaging modalities like ultrasound and fluoroscopy instead of only simultaneously displaying these images on separate screens. Therefore, several technical solutions for fusion imaging have been established that are nowadays commercially available [ 3 – 5 ]. However, to date, there are only a very limited number of studies which have shown the feasibility and safety of dynamic fusing imaging of TEE and fluoroscopy during cardiac interventions [ 6 ], and only one small study with a number limitations has pointed out towards a clinical advantage of the use of FI during interventional LAA closure [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other imaging modalities with potential to improve endovascular guidance are magnetic resonance imaging (MRI), computed tomography (CT) and 3d rotational X-ray angiography, typically performed pre-operatively. Fusing multiple imaging modalities and developing computer vision techniques to enhance tool visualization can lead to accurate and robust localization of the catheter, with reduced use of fluoroscopy [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . In many situations this requires registration of 3d pre-operative data to 2d intra-operative fluoroscopy images, of which a key aspect is the ability to accurately localize and segment the catheter in the X-ray fluoroscopic images.…”
Section: Introductionmentioning
confidence: 99%
“…The EchoNavigator software has been used previously in percutaneous interventions for structural heart disease including: transapical TAVI procedures, atrial septal defect closure, left atrial appendage closure and mitral valve clip procedures. 7 Our report highlights how fusion of real-time TEE and fluoroscopy imaging with the EchoNavigator system facilitates transcatheter paravalvular leak closure. Improved imaging guides the procedure making it quicker and safer leading to better outcomes.…”
Section: Commentmentioning
confidence: 89%